2016
DOI: 10.1152/ajprenal.00306.2016
|View full text |Cite
|
Sign up to set email alerts
|

Aging-associated renal disease in mice is fructokinase dependent

Abstract: Aging-associated kidney disease is usually considered a degenerative process associated with aging. Recently, it has been shown that animals can produce fructose endogenously, and that this can be a mechanism for causing kidney damage in diabetic nephropathy and in association with recurrent dehydration. We therefore hypothesized that low-level metabolism of endogenous fructose might play a role in aging-associated kidney disease. Wild-type and fructokinase knockout mice were fed a normal diet for 2 yr that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…A limitation of our study was that we used a genetically modified (fructokinase knockout) mouse to show a functional role of fructokinase in high-salt-mediated obesity. However, these mice show normal activity and development and have a normal life span (29). They are also protected against fructose-induced obesity (9) but not against obesity driven by a high-fat diet (30), which supports the finding that high-salt diets may induce obesity via endogenous fructose production.…”
Section: Discussionsupporting
confidence: 65%
“…A limitation of our study was that we used a genetically modified (fructokinase knockout) mouse to show a functional role of fructokinase in high-salt-mediated obesity. However, these mice show normal activity and development and have a normal life span (29). They are also protected against fructose-induced obesity (9) but not against obesity driven by a high-fat diet (30), which supports the finding that high-salt diets may induce obesity via endogenous fructose production.…”
Section: Discussionsupporting
confidence: 65%
“…We did not study other properties of H 2 S that may be potentially involved in amelioration of kidney injury, e.g., mitochondrial biogenesis and regulation of epigenetics (Weber et al 2017). In future, we will need to address the role of H 2 S in recently reported mechanisms of kidney injury in aging, e.g., podocyte deficiency leading to glomerulosclerosis, mitochondrial dysfunction, and fructose metabolism (Hodgin et al 2015;Roncal-Jimenez et al 2016;Sweetwyne et al 2017). Additionally, we did not test whether H 2 S prolongs life span in mice as has been shown in C elegans (Miller et al 2011;Miller and Roth 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, resveratrol prolongs lifespan in the extremely short-lived killifish (90). We found that mice that cannot generate fructose, which are therefore protected from mitochondrial oxidative stress, were also protected from developing age-related renal disease (157). In theory, elevated expression of NRF2 also mimics caloric restriction, as knockdown of KEAP1 in mice results in accumulation of NRF2 and thus augments the activation of cellular stress responses, including fatty acid oxidation and lipogenesis (158) .…”
Section: [H1] Ageing and Longevitymentioning
confidence: 90%